Re-visiting the Easterlin hypothesis: Marriage in the US 1968 - 2010 - Diane Macunovich (Institute for the Study of Labor (IZA), 2011)
This study tests the effect of relative income - younger people's earning potential relative to their aspirations, as approximated by older families' income - on the proportions married, by sex, in the first fifteen years out of school. It finds that relative income has become a better measure to use, than relative cohort size, because of a disconnect that has developed between the two as a result of rising female labor force participation among older women that has inflated older families' income faster than older men's earnings. The results are highly supportive of the Easterlin relative income hypothesis, finding a dominant negative effect of older family income that extends due to postponement effects even into groups 11-15 years out of school. But in addition it finds a strong but changing effect of the female wage: positive among women 0-5 years out of school, although slowly declining over time, but negative among the older women with a dominant positive time trend that has produced a positive effect in the last decade. The elasticity with respect to older family income suggests that it was responsible for 16% of the observed decline in the proportion of women 0-5 years out of school who were married, and 23% of the proportion for the men in the same group. There is in addition, however, a very strong negative time trend.
urn:nbn:de:101:1-201108093168
Keywords: J12; 330; marriage; relative income; relative cohort size; Easterlin hypothesis; marriage squeeze